The Solvability of the Boundary Value Problem of the Four Elements with the Carleman Shift and Complex-conjugate Values (Journal of Partial Differential Equations, 1997)
To following boundary value problem a(t)\overline{Φ^+(t)} + b(t)Φ^+[α(t)] + c(t)\overline{Φ^-(t)} + d(t)Φ^-[a(t)] = f(t) this paper has given out the number of linearly independent solutions and the conditions of solvability, so as to deepen the study of the problem to the same level as that of following problem a(t)\overline{Φ^+(t)} + b(t)Φ^+(t) + c(t)\overline{Φ^-(t)} + d(t)Φ^-(t) = f(t)
Keywords: Boundary value problem; Noether problem; number of linearly independent solutions; number of the conditions of solvability